Promoting Citizenship and Personal Growth: A Model for Student-Athlete Excellence - Del Giorno, Julie A.; Davis, Shala E.; Leitner, Donna L. (My University, 2002)
Many institutions of higher education are searching/or ways to augment specific areas of a student-athlete's life: such as study skills, fitness awareness, or disordered eating. East Stroudsburg University has developed a model that provided the additional support systems with the goal of developing not only a more competitive athlete but also a more mature and responsible member of the university community. This model included a physical and psycho-social component. A multi-discipline staff attempted to encourage the student-athletes with the life skills and the interaction to develop these tools for their life after college.
Keywords: models; student development